DETERMINAN TINGKAT SUKU BUNGA PINJAMAN PERBANKAN DI INDONESIA (PERIODE JULI 2005 – DESEMBER 2011) - Waljianah, Riza; Wulandari, Farah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
This paper describes the effect of monetary instruments BI rate in order to influence the movement of the loan interest rate through deposit interest rate and also explained the macroeconomic factors thought to affect the movement of the loan interest rate are interbank rates, inflation, as well as the variables associated with international financial interaction are exchange rate and foreign interest rate SIBOR. The analysis used multiple regression analysis incrementally with the study period July 2005 - December 2011.Empirical test results prove that the policy interest rate BI rate has a major impact or influence the development of interest rate loan through an interest rate of deposits. Interbank rates and SIBOR have the opposite effect in influencing the direction of loan interest rate through deposit interest rate. Inflation has no significant contribution in the movement of the loan interest rate. And exchange rate has little contribution with unidirectional movement in influencing of loan interest rate through interest rates on deposits. Keywords: BI Rate, interbank rates, inflation, exchange rates, SIBOR, loan interest rate.